A Flawed War: Rethinking 'Green Militarisation' in the Kruger National Park. (3rd May 2016) - Shaw, Mark; Rademeyer, Julian
ABSTRACT: Drawing on both a historical analysis of wildlife conservation in South Africa and the experience of other countries in Africa in countering wildlife poaching, some scholars have labelled the process of responding to rhino poaching in the Kruger National Park as 'green militarisation'. The term is broadly employed to denote the use of military-style techniques and approaches, as well as the military itself, in countering poaching. Several proponents of this approach have concluded that rhino trafficking has become increasingly defined in a 'national security' frame, with the result being that community orientated and other related responses are downplayed or not adopted. While there is evidence of the increased militarisation of the response in the Kruger National Park, we argue that the term 'green militarisation' runs the risk of simplifying what is in reality a complex and more contested process than is being given credit for. For 'green militarisation' to be retained as a successful analytical tool, at least in the context of the Kruger National Park, it requires drawing on a wider range of sources and a better understanding of processes of political and institutional change outside of the immediate conservation discussion.